Molecular mapping of stem and leaf rust resistance in wheat - Khan, R. R.; Bariana, Harbans S.; Dholakia, Bhushan B.; Naik, S. V.; Lagu, Meena D.; Rathjen, A. J.; Bhavani, Sridhar; Gupta, V. S. (Theoretical and Applied Genetics, 2005)
Stem rust caused by Puccinia graminis f. sp. tritici Eriks and Henn and leaf rust caused by Puccinia triticina Rob. ex Desm. are major constraints to wheat production worldwide. In the present study, F-4-derived SSD population, developed from a cross between Australian cultivars `Schomburgk' and `Yarralinka', was used to identify molecular markers linked to rust resistance genes Lr3a and Sr22. A total of 1,330 RAPD and 100 ISSR primers and 33 SSR primer pairs selected on the basis of chromosomal locations of these genes were used. The ISSR marker UBC 840(540) was found to be linked with Lr3a in repulsion at a distance of 6.0 cM. Markers cfa2019 and cfa2123 flanked Sr22 at a distance of 5.9 cM (distal) and 6.0 cM (proximal), respectively. The use of these markers in combination would predict the presence or absence of Sr22 in breeding populations. A previously identified PCR-based diagnostic marker STS638 linked to Lr20 was validated in this population. This marker showed a recombination value of 7.1 cM with Lr20.

Molecular genetic mapping of quantitative trait loci associated with loaf volume in hexaploid wheat (Triticum aestivum) - Elangovan, M.; Rai, R.; Dholakia, Bhushan B.; Lagu, Meena D.; Tiwari, R.; Gupta, R. K.; Rao, V. S.; Roeder, M. S.; Gupta, V. S. (Journal of Cereal Science, 2008)
Major efforts in wheat research are being made to improve the yield and quality of wheat. Loaf volume (Lv) is the main quality parameter deciding the bread making potential of wheat. To genetically dissect quantitative trait loci (QTLs) for Lv, a Recombinant Inbred Line (RIL) population (F-8) was developed from a cross between two Indian wheat varieties ``H 1977'' and ``HD 2329''. A total of 914 SSR and 100 ISSR primers were used for molecular analysis and the genetic map comprising 19 chromosomes was constructed with 202 SSR markers and 2 HMW glutenin subunit loci: Glu-B1 and Glu-B1. The phenotypic data were collected from six environments including three different agro-climatic zones for 2 consecutive years. Dissection of Lv through AMMI model revealed significant G x E variance for the trait. QTL analysis was performed using composite interval mapping. A total of 30 QTLs for Lv were detected and significant QTLs were identified on 6B and 6D chromosomes; 1B, 1D, 2A, 3A, 513 and 5D also contributed genetically to Lv. Association between 6B and 6D QTLs and variable expression of gliadins on group 6 chromosomes were discussed. QTLs detected in this study were compared with other QTL analysis in wheat. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: breadmaking; loaf volume; QTL; SSR; wheat quality

Molecular mapping of leaf rust resistance gene Lr15 in hexaploid wheat - Dholakia, Bhushan B.; Rajwade, A. V.; Hosmani, P.; Khan, R. R.; Chavan, S.; Reddy, D. M. R.; Lagu, Meena D.; Bansal, Urmil K.; Saini, R. G.; Gupta, V. S. (Molecular Breeding, 2013)
Leaf rust is a widespread and commonly occurring rust disease of wheat. Genetic resistance is the most economical method of reducing losses due to leaf rust. Lr15 has been shown to be present on wheat chromosome 2D and is reported to be a seedling resistance gene. However, tightly linked markers associated with Lr15 have not been reported to date. To identify molecular markers linked to Lr15, an F-2 mapping population of Thatcher x Thatcher-Lr15 was generated. Available wheat simple sequence repeat markers were utilized in parental screening and polymorphic markers were used to analyze the entire population of 221 plants. Phenotypic evaluations of the F-2-derived F-3 progenies with Puccinia triticina Eriks. pathotype 162A (93R15) confirmed the monogenic inheritance of Lr15. The linkage group representing chromosome 2DS was constructed at LOD 4.0 which revealed the closest flanking markers Xgwm4562 and Xgwm102 at a distance of 3.1 and 9.3 cM, respectively. Furthermore, utilization of these flanking markers in combination has successfully identified wheat lines with or without Lr15. These markers could potentially be useful in gene pyramiding with other genes to enhance rust resistance in wheat.
Keywords: Disease resistance; Leaf rust; Marker-assisted selection; Simple sequence repeat; Wheat